2022
DOI: 10.1088/1748-9326/ac4940
|View full text |Cite
|
Sign up to set email alerts
|

Global temperature goals should determine the time horizons for greenhouse gas emission metrics

Abstract: Emission metrics, a crucial tool in setting effective exchange rates between greenhouse gases, currently require an arbitrary choice of time horizon. Here, we propose a novel framework to calculate the time horizon that aligns with scenarios achieving a specific temperature goal. We analyze the Intergovernmental Panel on Climate Change Special Report on Global Warming of 1.5 °C Scenario Database to find that time horizons aligning with the 1.5 °C and 2 °C global warming goals of the Paris Agreement are 24 [90%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Reporting these pollutants separately allows for consideration not only of potential effects of mitigation measures by source and implications for coemissions but also an assessment of temperature impact on multiple time horizons of interest ( 1 ). With 1.5 °C expected to be crossed in the early 2030s ( 1 , 38 ), Abernethy and Jackson ( 39 ) have advocated for choosing time horizons for GHG aggregation metrics consistent with temperature goals, specifically supporting the use of GWP 20 over the GWP 100 . A similar argument can be made in the context of the urgency to slow warming in the near term ( 2 ).…”
Section: Contributions To Radiative Forcing: Co 2 ...mentioning
confidence: 99%
“…Reporting these pollutants separately allows for consideration not only of potential effects of mitigation measures by source and implications for coemissions but also an assessment of temperature impact on multiple time horizons of interest ( 1 ). With 1.5 °C expected to be crossed in the early 2030s ( 1 , 38 ), Abernethy and Jackson ( 39 ) have advocated for choosing time horizons for GHG aggregation metrics consistent with temperature goals, specifically supporting the use of GWP 20 over the GWP 100 . A similar argument can be made in the context of the urgency to slow warming in the near term ( 2 ).…”
Section: Contributions To Radiative Forcing: Co 2 ...mentioning
confidence: 99%
“…In their comment, Romano et al use both 20‐ and 100‐year global warming potentials but fail to emphasize the superiority of the 20‐year time frame for avoiding immediate damage and tipping points for more severe long‐term damage. Along those lines, Abernethy and Jackson 29 in a new 2022 paper have demonstrated that the use of a 100‐year GWP is simply not compatible with reaching the climate goals set by the COP21 Paris accords in 2015.…”
Section: Global Warming Potentialmentioning
confidence: 99%
“…GWP provides a single number that enables 'apples to apples' evaluation of any SLCP by directly comparing its potency to the potency of carbon dioxide. Additionally, numerous alternative metrics have been proposed, each designed to evaluate different aspects of the climate system [4,[8][9][10][11][12][13][14][15][16][17][18][19]. As reviewed by Balcombe [4], these metrics evaluate different timeframes, physical bases, emission durations, and more.…”
Section: Traditional Emission Metricsmentioning
confidence: 99%
“…PGW leverages the thoughtful analysis used for discount rate selection to give a value that is both justifiable and consistent with other considerations. Temporal weighting values, such as time horizons in GWP and discount rates in PGW, reflect societal preferences and are mostly political selections [15,23]. Today there is some consensus on the political choice of discount rate used in climate policy, and that same chosen discount rate could be used for PGW.…”
Section: Pgwmentioning
confidence: 99%
See 1 more Smart Citation